Analisis Kebutuhan Buku Panduan Lapang Interaktif Berbasis Problem Based Learning pada Mata Kuliah Entomologi - Rahmawati, Suci (Al Jahiz, 2024)
There is no relevant learning resource in the form of a problem-based field guide on the entomologi. The purpose of this study is to analyze how important the need for interactive field guide based on problem-based learning is to the ability to solve problems. This research method is descriptive qualitative with a questionnaire to students and lecturers through google form and direct interviews. The results of the research obtained based on (1). Analysis of learning objectives needs to add the role of insect pollinators positively; (2) needs analysis states 74% of students stated that reference books based on problem-based learning are very important (3). teaching lecturers also agree to develop field guide books linking problems with the results of research obtained; (4). The tasks presented in this field guidebook are mini research tasks that can be used as guidelines for the application of tasks that apply at the University. It is concluded that lecturers and students need an interactive field guide to pollinating insect behavior in tomato plants (Solanum lycopersicum) based on problem-based learning.